Microplastic Munchies: Exploring Microplastic Trophic Transfer Potential Between Two Key Prey Fish Species and Resident Common Bottlenose Dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida - Estella Martin; Randall S. Wells; Elizabeth J. Berens McCabe; Miranda K. Dziobak; Savannah M. Case; Tita Curtin; Eric Conger; Ayushi Gaur; Millie A. Knowles; Robyn Faulkner Allen; Christina N. Toms; John E. Weinstein; et al. (Marine Mammal Science, 2026)
Microplastics have been identified in hundreds of species, with evidence of trophic transfer via contaminated prey. Sarasota Bay common bottlenose dolphins ( Tursiops truncatus ) serve as sentinels of coastal pollution, including plastics and chemical plasticizers. Previous research confirmed microplastic ingestion in these dolphins (100.0%, n = 7) and extensive contamination in 11 common prey species (96.5%, n = 86). This study compared microplastic characteristics in dolphins, Gulf toadfish ( Opsanus beta , n = 30) and pinfish ( Lagodon rhomboides , n = 35), to assess potential trophic transfer. Dolphin ingestion was evaluated using gastric ( n = 23) and fecal ( n = 15) samples from catch‐and‐release health assessments (2022–2024), while prey gastrointestinal and muscle tissues were screened. Particles were prevalent across samples (dolphins: 82.6%, pinfish: 97.1%, toadfish: 96.7%), with fibers as the dominant shape. Raman spectroscopy confirmed plastic polymers (PL, PP, and PET) in all species. Pinfish had a higher median particle load (1.4 particles/g tissue) than toadfish (0.6 particles/g tissue; p = 0.006). Based on estimated daily food intake (5.96–6.45 kg) and diet composition (toadfish—34.1%, pinfish—38.1%), Sarasota dolphins may ingest more than 10,000 particles/day from these fish alone. Contaminated prey may be vectors for dolphin microplastic exposure. This study emphasizes the need for further research on microplastic pathways in marine food webs and implications for wildlife.

Impacts of nature relatedness and motivation on active outdoor recreation participation - Megan K. McCabe; Sammie L. Powers; Julie S. Son (Journal of Outdoor Recreation and Tourism, 2026)

Adsorption-style rate kinetics best describes long chain fatty acid inhibition of methanogenesis - Christopher H. Bühlmann; Sergi Astals; Bede S. Mickan; Bernadette K. McCabe; Stephan Tait (Bioresource Technology, 2026)

Technoeconomic feasibility of integrated organics processing facilities with anaerobic digestion and composting: An analytical framework for regional Australia - Fred Williams; Peter Harris; Stephan Tait; Bede S. Mickan; Wolfgang Merkle; Hans-Joachim Nägele; Bernadette K. McCabe (Waste Management, 2025)

Sedimentation in Saudi Arabia’s 574 reservoirs: Nationwide assessment using remote sensing and erosion modeling - Sonam S. Dash; Nikola Ivanović; Raied Alharbi; Gregory R. Hancock; Yoshihide Wada; Matthew F. McCabe; Debasish Pal; Hannu Marttila; Hylke E. Beck (Journal of Environmental Management, 2025)

Salicylaldehyde Benzoylhydrazone Protects Against Ferroptosis in Models of Neurotoxicity and Behavioural Dysfunction, In Vitro and In Vivo - Niamh C. Clarke; Ellen McCabe; Lasse D. Jensen; Bernadette S. Creaven; Derek A. Costello (Journal of Molecular Neuroscience, 2025)
Metal dyshomeostasis in the brain is a key feature of many neuropathologies, including hypoxic and traumatic injury and chronic conditions such as Alzheimer’s and Parkinson’s disease. Ferroptosis is a form of cell death driven by the intracellular accumulation of iron. This is primarily characterised by a loss in endogenous antioxidant capacity and uncontrolled lipid peroxidation. Ferroptosis has been reported to underlie the pathology associated with several neurological and neurodegenerative conditions and has, therefore, become an attractive target for therapeutic intervention. Salicylaldehyde benzoylhydrazone (SBH) is a specialised hydrazone agent, known for its antibacterial and anticancer properties. It has robust metal-chelating capacity, with a particular affinity for complexing with iron and copper. The current study sought to investigate the potential of SBH to act as an anti-ferroptotic agent and to alleviate the neurotoxic and dysfunctional consequences of iron overload. We demonstrate that SBH can alleviate the death of HT22 hippocampal neurons, induced by exposure to the iron donor, ferric ammonium citrate (FAC). This was accompanied by a reduction in intracellular iron and lipid peroxidation, and alleviation of hallmark changes in gene expression indicative of ferroptosis. Using FAC-incubated zebrafish larvae as an in vivo model of iron overload, we reveal that SBH can reduce the mortality and toxicity associated with FAC exposure. Moreover, we report a FAC-mediated dysfunction in intrinsic sensorimotor reflex behaviour, which is restored by SBH. Taken together, our findings highlight SBH as an anti-ferroptotic agent and support its further investigation as a potential neurotherapeutic for conditions associated with iron dysregulation.

Global estimates of daily evapotranspiration using SMAP surface and root-zone soil moisture - Youngwook Kim; Hotaek Park; John S. Kimball; Andreas Colliander; Matthew F. McCabe (Remote Sensing of Environment, 2023)

The skin barrier: An extraordinary interface with an exceptional lipid organization - Joke A. Bouwstra; Andreea Nădăban; Wim Bras; Clare McCabe; Annette Bunge; Gerrit S. Gooris (Progress in Lipid Research, 2023)

Degradation rates influence the ability of composite samples to represent 24-hourly means of SARS-CoV-2 and other microbiological target measures in wastewater - Kristina M. Babler; Mark E. Sharkey; Samantha Abelson; Ayaaz Amirali; Aymara Benitez; Gabriella A. Cosculluela; George S. Grills; Naresh Kumar; Jennifer Laine; Walter Lamar; Erik D. Lamm; Jiangnan Lyu; et al. (Science of The Total Environment, 2023)

A hydrologic perspective of major U.S. droughts - Gregory J. McCabe; David M. Wolock; Melissa Lombard; Robert W. Dudley; John C. Hammond; Jory S. Hecht; Glenn A. Hodgkins; Carolyn Olson; Roy Sando; Caelan Simeone; Mike Wieczorek (International Journal of Climatology, 2023)
Drought is a recurring natural hazard that has substantial human and environmental impacts. Given continued global warming and associated climate change, there is concern that droughts could become more severe and longer lasting. To better monitor and understand drought development and persistence, it is helpful to understand the development and climatic drivers of past droughts. In this study we use monthly runoff percentiles to identify five major drought events in the conterminous United States (CONUS) from 1901 through 2020. For each drought event we examined spatial patterns of departures of mean monthly precipitation, temperature, soil moisture storage, and runoff for 2,107 hydrologic units (HUs) across the CONUS. Results indicated that precipitation deficits have been the primary driver of past major‐drought events and temperature a secondary driver, even of the most recent drought event (September 1999 through September 2015) when positive temperature anomalies occurred over most of the CONUS. Additionally, negative soil moisture storage departures were more negative than runoff departures during the five drought events we examined, which emphasizes the importance of measuring both runoff and soil moisture to monitor drought conditions. We also examined the use of statistical persistence to develop short‐term (i.e., 1 month) forecasts of runoff drought conditions in the CONUS by developing autoregressive integrated moving average (ARIMA) models for each HU. Results indicated that persistence can be used to predict short‐term changes in the spatial pattern of drought and the areal extent of drought, but that predictions of runoff magnitude for any particular site are often poor.

Phenotyping a diversity panel of quinoa using UAV-retrieved leaf area index, SPAD-based chlorophyll and a random forest approach - Jiale Jiang; Kasper Johansen; Clara S. Stanschewski; Gordon Wellman; Magdi A. A. Mousa; Gabriele M. Fiene; Khalid A. Asiry; Mark Tester; Matthew F. McCabe (Precision Agriculture, 2022)
Given its high nutritional value and capacity to grow in harsh environments, quinoa has significant potential to address a range of food security concerns. Monitoring the development of phenotypic traits during field trials can provide insights into the varieties best suited to specific environmental conditions and management strategies. Unmanned aerial vehicles (UAVs) provide a promising means for phenotyping and offer the potential for new insights into relative plant performance. During a field trial exploring 141 quinoa accessions, a UAV-based multispectral camera was deployed to retrieve leaf area index (LAI) and SPAD-based chlorophyll across 378 control and 378 saline-irrigated plots using a random forest regression approach based on both individual spectral bands and 25 different vegetation indices (VIs) derived from the multispectral imagery. Results show that most VIs had stronger correlation with the LAI and SPAD-based chlorophyll measurements than individual bands. VIs including the red-edge band had high importance in SPAD-based chlorophyll predictions, while VIs including the near infrared band (but not the red-edge band) improved LAI prediction models. When applied to individual treatments (i.e. control or saline), the models trained using all data (i.e. both control and saline data) achieved high mapping accuracies for LAI (R 2 = 0.977–0.980, RMSE = 0.119–0.167) and SPAD-based chlorophyll (R 2 = 0.983–0.986, RMSE = 2.535–2.861). Overall, the study demonstrated that UAV-based remote sensing is not only useful for retrieving important phenotypic traits of quinoa, but that machine learning models trained on all available measurements can provide robust predictions for abiotic stress experiments.

Coupling plant litter quantity to a novel metric for litter quality explains C storage changes in a thawing permafrost peatland - Moira Hough; Samantha McCabe; S. Rose Vining; Emily Pickering Pedersen; Rachel M. Wilson; Ryan Lawrence; Kuang‐Yu Chang; Gil Bohrer; William J. Riley; Patrick M. Crill; Ruth K. Varner; Steven J. Blazewicz; et al. (Global Change Biology, 2022)
Permafrost thaw is a major potential feedback source to climate change as it can drive the increased release of greenhouse gases carbon dioxide (CO 2 ) and methane (CH 4 ). This carbon release from the decomposition of thawing soil organic material can be mitigated by increased net primary productivity (NPP) caused by warming, increasing atmospheric CO 2 , and plant community transition. However, the net effect on C storage also depends on how these plant community changes alter plant litter quantity, quality, and decomposition rates. Predicting decomposition rates based on litter quality remains challenging, but a promising new way forward is to incorporate measures of the energetic favorability to soil microbes of plant biomass decomposition. We asked how the variation in one such measure, the nominal oxidation state of carbon (NOSC), interacts with changing quantities of plant material inputs to influence the net C balance of a thawing permafrost peatland. We found: (1) Plant productivity (NPP) increased post‐thaw, but instead of contributing to increased standing biomass, it increased plant biomass turnover via increased litter inputs to soil; (2) Plant litter thermodynamic favorability (NOSC) and decomposition rate both increased post‐thaw, despite limited changes in bulk C:N ratios; (3) these increases caused the higher NPP to cycle more rapidly through both plants and soil, contributing to higher CO 2 and CH 4 fluxes from decomposition. Thus, the increased C‐storage expected from higher productivity was limited and the high global warming potential of CH 4 contributed a net positive warming effect. Although post‐thaw peatlands are currently C sinks due to high NPP offsetting high CO 2 release, this status is very sensitive to the plant community's litter input rate and quality. Integration of novel bioavailability metrics based on litter chemistry, including NOSC, into studies of ecosystem dynamics, is needed to improve the understanding of controls on arctic C stocks under continued ecosystem transition.

Decreased bee emergence along an elevation gradient: Implications for climate change revealed by a transplant experiment - Lindsie M. McCabe; Clare E. Aslan; Neil S. Cobb (Ecology, 2022)
Bees experience differences in thermal tolerance based on their geographical range; however, there are virtually no studies that examine how overwintering temperatures may influence immature survival rates. Here, we conducted a transplant experiment along an elevation gradient to test for climate‐change effects on immature overwinter survival using movement along elevational gradient for a community of 26 cavity‐nesting bee species in the family Megachilidae along the San Francisco Peaks, Arizona elevational gradient. In each of three years, we placed nest blocks at three elevations, to be colonized by native Megachilidae. Colonized blocks were then (1) moved to lower (warmer) elevations; (2) moved to higher (cooler) elevations; or (3) left in their natal habitat (no change in temperature). Because Megachilidae occupy high elevations with colder temperatures more than any other family of bees, we predicted that emergence would decrease in nest blocks moved to lower elevations, but that we would find no differences in emergence when nest blocks were moved to higher elevations. We found three major results: (1) Bee species moved to lower (warmer) habitats exhibited a 30% decrease in emergence compared with species moved within their natal habitat. (2) Habitat generalists were more likely than habitat specialists to emerge when moved up or down in elevation regardless of their natal life zones. (3) At our highest elevation treatment, emergence increased when blocks were moved to higher elevations, indicating that at least some Megachilidae species can survive at colder temperatures. Our results suggest that direct effects of warming temperatures will have negative impacts on the overall survival of Megachilidae. Additionally, above the tree line, low availability of wood‐nesting resources is a probable limiting factor on bees moving up in elevation.

Effects of Multiple Karenia brevis Red Tide Blooms on a Common Bottlenose Dolphin (Tursiops truncatus) Prey Fish Assemblage: Patterns of Resistance and Resilience in Sarasota Bay, Florida - Elizabeth J. Berens McCabe; Randall S. Wells; Christina N. Toms; Aaron A. Barleycorn; Krystan A. Wilkinson; Valeriy I. Palubok (Frontiers in Marine Science, 2021)
Red tide blooms caused by the toxic dinoflagellate Karenia brevis are natural disturbance events that occur regularly along Florida’s west coast, often resulting in massive fish kills and marine mammal, seabird, and sea turtle mortalities. Limited prior work on the ecological effects of red tides suggests they play an important role in structuring ecosystem dynamics and regulating communities, however specific effects on prey populations and potential alterations to predator-prey interactions are unknown. We surveyed the prey fish assemblage of a top marine predator, the common bottlenose dolphin ( Tursiops truncatus ), in shallow seagrass habitat in Sarasota Bay, Florida, during 2004–2019, collecting data on prey density, species composition, K. brevis cell densities, and environmental variables. Across eight distinct red tide bloom events, resistance, resilience, and the ecological effects on the prey assemblage varied depending on bloom intensity, season, and frequency. Prey assemblage structure showed significant and distinct short-term shifts during blooms independent of the normal seasonal shifts in prey structure seen during non-bloom conditions. Canonical correspondence analysis indicated a strong influence of K. brevis density on assemblage structure. Blooms occurring primarily in the summer were associated with less initial prey resistance and higher than average annual catch per unit effort (CPUE) 1–3 years following bloom cessation, with bloom frequency prolonging the time needed to reach higher than average annual CPUE. Regardless of season, recovery to pre-bloom prey abundances occurred within 1 year. Sample-based rarefaction and extrapolation indicated significant differences in prey diversity among summer bloom events. This study is a first step in identifying differences in resistance, resilience, and the ecological effects of multiple red tide bloom events of various temporal scales and intensity on a dolphin prey assemblage. Improved understanding of the influence of red tides on estuarine structural dynamics and function can better inform management, and potentially guide mitigation efforts post-bloom.

Body Composition of Common Bottlenose Dolphins in Sarasota Bay, Florida - Stephanie K. Adamczak; Rachel R. Holser; Daniel P. Costa; Elizabeth J. Berens McCabe; Randall S. Wells (Frontiers in Marine Science, 2021)
Marine mammal body composition has been an important tool that is used as a proxy for the health and condition of individuals within a population. Common bottlenose dolphin ( Tursiops truncatus ) body composition is influenced by variations in blubber thickness resulting from changes in temperature, prey availability, health, and life-history traits. We examined how environmental, ontogenetic, and reproductive variables influenced the body composition of common bottlenose dolphins in Sarasota Bay using data collected from a long-term monitoring project by the Sarasota Dolphin Research Program (SDRP). We found that both sea surface temperature (SST) and catch per unit effort (CPUE), used as a proxy for prey availability, influenced body composition. There was a high degree of seasonality in body composition, with higher values occurring in winter when SST and CPUE were both low. Ontogeny also greatly influenced body composition, as younger dolphins typically had thicker blubber than mature individuals. Interestingly, young females allocated more energy to allometric growth than deposition of blubber for body composition when compared to young males. However, as females matured and their growth slowed, they invested more in body composition. We found no significant difference in body composition of females of varying reproductive states, providing further evidence of their status as true income breeders. Our work highlights that changes in body composition result from fluctuations in environmental variables and that energy allocation to body composition changes with ontogeny.

Change in CSF Dynamics Responsible for ICP Elevation After Ischemic Stroke in Rats: a New Mechanism for Unexplained END? - Mohammed S. Alshuhri; Lindsay Gallagher; Christopher McCabe; William M. Holmes (Translational Stroke Research, 2020)

Spatial assessment of the performance of multiple high‐resolution satellite‐based precipitation data sets over the Middle East - Ahmed M. El Kenawy; Matthew F. McCabe; Juan I. Lopez‐Moreno; Yossef Hathal; S. M. Robaa; Ahmed L. Al Budeiri; Khan Zaib Jadoon; Abdou Abouelmagd; Ali Eddenjal; Fernando Domínguez‐Castro; Ricardo M. Trigo; Sergio M. Vicente‐Serrano (International Journal of Climatology, 2019)
This study presents the first comprehensive evaluation of the performance of three globally high‐resolution remotely sensed products in replicating the main characteristics of rainfall over the Middle East, with special emphasis on extreme wet events. Specifically, we employed daily observational data from a network of rain gauges ( N = 217), spanning the retrospective period 1998–2013 and covering six countries in the Middle East (i.e., Egypt, Iraq, Jordan, Libya, Saudi Arabia, and Syria), against data derived from three global satellite‐based precipitation products: the Version 7 TRMM (Tropical Rainfall Measuring Mission) Multi‐satellite Precipitation Analysis 3B42 product (TRMM‐3B42), the Climate Prediction Center MORPHing technique (CMORPH), and the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN). Alongside a range of conventional statistical error measures (e.g., bias, normalized root‐mean‐square error [nRMSE] and Spearman's rho correlation coefficient), this study also gives priority to evaluate the skill of these products in reproducing characteristics of extreme wet events (e.g., frequency, intensity, duration, onset, anomaly). Results demonstrate that TRMM‐3B42 generally performs well in estimating rainfall totals during the rainy season (ONDJFMA), with a mean bias of 0.05 mm, nRMSE of 0.15 mm, and Spearman's rho of 0.74 for the whole Middle East. In contrast, PERSIANN‐CDR and CMORPH‐BLD underestimate the observed rainfall. Importantly, TRMM‐3B42 outperforms other products in reproducing the frequency and intensity of the most extreme wet events, while PERSIANN‐CDR and CMORPH‐BLD fail to reproduce these key characteristics. Notably, all products perform poorly in reproducing the climatology of the anomalous wet events in the region, indicating that careful scrutiny must be warranted before using these products, particularly for hydrological modelling. Considering the daily resolution of these remotely sensed precipitation products and their reasonable spatial resolution (0.25 × 0.25°) in comparison to available in situ data over the Middle East, results of this work provide a solid scientific reference for national stakeholders and policy makers to decide on the most useful product for their specific applications (e.g., hydrological modelling, streamflow forecasts, water resources management, and hydrometeorological hazard assessment and mitigation).

Sexually Dimorphic Effects of Early-Life Exposures to Endocrine Disruptors: Sex-Specific Epigenetic Reprogramming as a Potential Mechanism - Carolyn McCabe; Olivia S. Anderson; Luke Montrose; Kari Neier; Dana C. Dolinoy (Current Environmental Health Reports, 2017)

Downscaling the 2D Bénard convection equations using continuous data assimilation - M. U. Altaf; E. S. Titi; T. Gebrael; O. M. Knio; L. Zhao; M. F. McCabe; I. Hoteit (Computational Geosciences, 2017)

Anxiety is related to indices of cortical maturation in typically developing children and adolescents - Erik Newman; Wesley K. Thompson; Hauke Bartsch; Donald J. Hagler; Chi-Hua Chen; Timothy T. Brown; Joshua M. Kuperman; Connor McCabe; Yoonho Chung; Ondrej Libiger; Natacha Akshoomoff; Cinnamon S. Bloss; et al. (Brain Structure and Function, 2016)

U–Pb zircon age of the Walloon Coal Measures in the Surat Basin, southeast Queensland: implications for paleogeography and basin subsidence - C. C. Wainman; P. J. Mccabe; J. L. Crowley; R. S. Nicoll (Australian Journal of Earth Sciences, 2015)

To what extent do long-duration high-volume dam releases influence river–aquifer interactions? A case study in New South Wales, Australia - P. W. Graham; M. S. Andersen; M. F. McCabe; H. Ajami; A. Baker; I. Acworth (Hydrogeology Journal, 2015)

Foraging habits in a generalist predator: Sex and age influence habitat selection and resource use among bottlenose dolphins ( Tursiops truncatus ) - Sam Rossman; Elizabeth Berens McCabe; Nélio B. Barros; Hasand Gandhi; Peggy H. Ostrom; Craig A. Stricker; Randall S. Wells (Marine Mammal Science, 2015)
This study examines resource use (diet, habitat use, and trophic level) within and among demographic groups (males, females, and juveniles) of bottlenose dolphins ( Tursiops truncatus ). We analyzed the δ 13 C and δ 15 N values of 15 prey species constituting 84% of the species found in stomach contents. We used these data to establish a trophic enrichment factor ( TEF ) to inform dietary analysis using a Bayesian isotope mixing model. We document a TEF of 0‰ and 2.0‰ for δ 13 C and δ 15 N, respectively. The dietary results showed that all demographic groups relied heavily on low trophic level seagrass‐associated prey. Bayesian standard ellipse areas ( SEA b ) were calculated to assess diversity in resource use. The SEA b of females was nearly four times larger than that of males indicating varied resource use, likely a consequence of small home ranges and habitat specialization. Juveniles possessed an intermediate SEA b , generally feeding at a lower trophic level compared to females, potentially an effect of natal philopatry and immature foraging skills. The small SEA b of males reflects a high degree of specialization on seagrass associated prey. Patterns in resource use by the demographic groups are likely linked to differences in the relative importance of social and ecological factors.

Imaging and Clinical Evidence of Sensorimotor Problems in CRPS: Utilizing Novel Treatment Approaches - Jacqueline Bailey; Sara Nelson; Jenny Lewis; Candida S. McCabe (Journal of Neuroimmune Pharmacology, 2013)

Low temperature conditions in building sandstone: the role of extreme events in temperate environments - D. McAllister; S. McCabe; B.J. Smith; S. Srinivasan; P.A. Warke (European Journal of Environmental and Civil Engineering, 2013)

Mathematical Simulation of Membrane Protein Clustering for Efficient Signal Transduction - Krishnan Radhakrishnan; Ádám Halász; Meghan M. McCabe; Jeremy S. Edwards; Bridget S. Wilson (Annals of Biomedical Engineering, 2012)

Erratum to: Prey selection by resident common bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Elizabeth J. Berens McCabe; Damon P. Gannon; Nélio B. Barros; Randall S. Wells (Marine Biology, 2010)

Prey selection by resident common bottlenose dolphins (tursiops truncatus) in Sarasota Bay, Florida - Elizabeth J. Berens McCabe; Damon P. Gannon; Nélio B. Barros; Randall S. Wells (Marine Biology, 2010)

Plant-based strategies aimed at expressing HIV antigens and neutralizing antibodies at high levels. Nef as a case study - Carla Marusic; Alessandro Vitale; Emanuela Pedrazzini; Marcello Donini; Lorenzo Frigerio; Ralph Bock; Philip J. Dix; Matthew S. McCabe; Michele Bellucci; Eugenio Benvenuto (Transgenic Research, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

An Intercomparison of Large-Eddy Simulations of the Stable Boundary Layer - Robert J. Beare; Malcolm K. Macvean; Albert A. M. Holtslag; Joan Cuxart; Igor Esau; Jean-Christophe Golaz; Maria A. Jimenez; Marat Khairoutdinov; Branko Kosovic; David Lewellen; Thomas S. Lund; Julie K. Lundquist; et al. (Boundary-Layer Meteorology, 2006)

Stable Plastid Transformation in Lettuce (Lactuca sativa L.) - Cilia L. C. Lelivelt; Matthew S. McCabe; Christine A. Newell; C. Bastiaan deSnoo; Kees M. P. van Dun; Ian Birch-Machin; John C. Gray; Kingston H. G. Mills; Jacqueline M. Nugent (Plant Molecular Biology, 2005)

Depositional and post‐depositional history of warm stage deposits at Knocknacran, Co. Monaghan, Ireland: implications for preservation of Irish last interglacial deposits - A. P. M. Vaughan; L. A. Dowling; F. J. G. Mitchell; S.‐E. Lauritzen; A. M. McCabe; P. Coxon (Journal of Quaternary Science, 2004)
Organic‐rich deposits, uncovered during overburden removal from mantled gypsum karst at Knocknacran opencast gypsum mine, Co. Monaghan, are the best candidate to date for a last interglacial record in Ireland. The two till and organic‐rich deposits (preserved at different quarry elevations) were emplaced on to a Tertiary dolerite surface during high‐energy flood events and subsequently folded and faulted by movement towards sinkholes in underlying gypsum. Uranium–thorium disequilibrium dating suggests that the organic‐rich deposits in the upper section were hydrologically isolated at ca. 41 ka and those in the lower section at ca. 86 ka. Interpretation of the pollen content, although tentative because of the depositional and post‐depositional history of the material, suggests that the organic material originated in a warm stage possibly warmer than the post‐Eemian interstadials. The unusual setting of preservation may indicate that in situ , last interglacial deposits have generally been removed by erosion in Ireland. Copyright © 2004 John Wiley & Sons, Ltd.

Ammonia uptake and its effects on ionoregulation in the freshwater crayfish Pacifastacus leniusculus (Dana) - Harris R.; Coley S.; Collins S.; McCabe R. (Journal of Comparative Physiology B, 2001)

Glycerol kinase deficiency: Evidence for complexity in a single gene disorder - K. Dipple; Y.-H. Zhang; B.-L. Huang; L. McCabe; J. Dallongeville; T. Inokuchi; M. Kimura; H. Marx; G. Roederer; V. Shih; S. Yamaguchi; I. Yoshida; et al. (Human Genetics, 2001)

Agrobacterium-mediated transformation of Lupinus mutabilis L. using shoot apical explants - Mehmet Babaoglu; Matthew S. McCabe; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2000)

Increased stable inheritance of herbicide resistance in transgenic lettuce carrying a petE promoter-bar gene compared with a CaMV 35S-bar gene - M. S. McCabe; F. Schepers; A. van der Arend; U. Mohapatra; A. M. M. de Laat; J. B. Power; M. R. Davey (Theoretical and Applied Genetics, 1999)

Expression of the Bar Gene Confers Herbicide Resistance in Transgenic Lettuce - Umaballava Mohapatra; Matthew S. McCabe; J. Brian Power; Frank Schepers; Aad Van Der Arend; Michael R. Davey (Transgenic Research, 1999)

Temporal relationships between leukocytes, IL-5 and IL-8 in guinea pig lungs, plasma cortisol and airway function after antigen challenge - H. Danahay; K. J. Broadley; P. J. McCabe; A. T. Nials; S. Sanjar (Inflammation Research, 1999)

Developmental expression of hexokinase 1 and 3 in rats - Katherine A. Coerver; S. M. Gray; James E. Barnes; Dawna L. Armstrong; E. R. B. McCabe (Histochemistry and Cell Biology, 1997)

Relationships between NADPH diaphorase staining and neuronal, endothelial, and inducible nitric oxide synthase and cytochrome P450 reductase immunoreactivities in guinea-pig tissues - H. M. Young; Anna J. O'Brien; John B. Furness; Daniela Ciampoli; James P. Hardwick; Timothy J. McCabe; Ramani Narayanasami; Bettie Sue S. Masters; W. Ross Tracey (Histochemistry and Cell Biology, 1997)

New signal processing techniques for improved precision of noninvasive impedance cardiography - J. H. Nagel; L. Y. Shyu; S. P. Reddy; B. E. Hurwitz; P. M. McCabe; N. Schneiderman (Annals of Biomedical Engineering, 1989)